Pelaksanaan Uji Kelayakan Jalan Becak - Muhammad Zalil Siregar; Sumper Mulia Harahap; Dermina Dalimunthe (IAIN Padangsidimpuan, 2021)
The background of this research problem is article 48 of law number 22 of 2009 concerning road traffic and transportation, there are rules regarding technical requirements and roadworthiness of motorized vehicles, but vehicles provided by rickshaw drivers produce noisy sounds and turn signals or indicator lights. direction so that it can interfere with other motorists, so that this is contrary to law number 22 of 2009 article 48 concerning road traffic and transportation.The formulation of the problem of this research is how to implement Law No. 22 of 2009 article 48 concerning roadworthiness tests for public vehicles (pedicabs) in Padangsidimpuan City and what factors are the obstacles in implementing Law No. 22 of 2009 article 48 regarding vehicle road feasibility tests. public rickshaws in the city of Padangsidimpuan.The purpose of this research is to find out the implementation of Law No. 22 of 2009 Article 48 regarding the roadworthiness test of public vehicles (becak) in Padangsidimpuan City, and also to find out what factors are obstacles in the implementation of Law No. 22 of 2009 Article 48 concerning road feasibility test for public vehicles (becak) in Padangsidimpuan City.This type of research is qualitative research. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words and highly observed behavior, while the approach used by the researcher is a sociological approach or socio-legal research method, namely